Credit policy management and the delinquent portfolio of the COOPACT of the District of Tocache San Martin: International literature article - Guerrero Veintemilla, Lady Margarita (2021)
This article sought to determine the effect of credit policy management on the behaviour of the delinquent portfolio in the COOPACT of the district of Tocache-San Martin, this study was applied type, non-experimental design, quantitative approach, cross-sectional and descriptive scope, the population and sample consisted of the Cooperative Savings and Credit, during the period 2017 to 2020; for data collection was used two study techniques documentary analysis and interview, with which it was obtained as a result that the financial institution has an adequate credit policy management, since in the years 2017 and 2018 have obtained favorable results, however, in the year 2019, employees have not exercised correctly credit policies generating an unfavorable increase in the rates of delinquent portfolio; instead in the year 2020 the financial institution applied strategic methods that helped mitigate the risk that could cause the pandemic managing to stabilize the indicators of the delinquent portfolio. It was concluded that the financial institution by adequately applying the credit policy management generates a positive effect on the behaviour of the non-performing portfolio.